Dialogic-interactive media: Alternative learning media to improve speaking skills - Atmazaki Atmazaki; Syahrul Ramadhan; Vivi Indriyani; Jeihan Nabila (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
The COVID-19 pandemic has not ended, so the learning process is still being carried out online. This results in ambiguity about how to teach. Language learning must be able to improve language skills, but some of these skills are difficult to teach. Based on the survey, speaking skills are the most difficult skills to teach online. Efforts are needed to overcome this, because speaking is considered the ultimate goal of language learning and the most basic skill to achieve. The purpose of this study was to develop dialogic-interactive media to improve students' speaking skills. The type of research used is development research using the Plomp Model (Preliminary Research, Prototype Phase, & Assessment Phase). Based on the research stages, the research objectives described in this article are to (1) describe the results of development research at the Preliminary Research stage and (2) describe the results of development research at the Prototyping Phase. The data analysis technique used in this research is descriptive data analysis technique. Based on the results of the study, it is shown that the use of learning methods and media in learning to speak has not helped students to improve their speaking skills. Therefore, interactive dialogical media were developed (introduction, interactive setting, everyday talk, learning talk, teaching talk, presenting; questioning; extending) and the teacher had a good response to the media model developed for use in learning to speak.